1988
DOI: 10.1080/02724988843000069
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Colour in Categorial Judgements

Abstract: Two experiments are reported that extend the findings of Ostergaard and Davidoff (1985) on the role of colour in object processing. Two types of categorial judgements were investigated from pictorial stimuli: size judgement and living/non-living classifications. The effect of real size on size judgements (Paivio, 1975) was replicated. It was found that colour did not affect either of the categorial judgements, but the facilitation occurring in object naming tasks was confirmed. It is argued that semantic judge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
3
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 22 publications
8
52
3
3
Order By: Relevance
“…These results are consistent with those of experiments measuring differences in accuracy between colored and black-and-white stimuli (Tanaka & Bunosky, 1993;Wurm et aI., 1993). They are also consistent with results of object identification and classification tasks showing that color facilitates reaction time for items that have learned colors (Davidoff & Ostergaard, 1988;Murphy, 1991;Ostergaard & Davidoff, 1985;Price & Humphreys, 1989;Tanaka & Bunosky, 1993). cific color value.…”
Section: Representation Of Colorsupporting
confidence: 76%
See 1 more Smart Citation
“…These results are consistent with those of experiments measuring differences in accuracy between colored and black-and-white stimuli (Tanaka & Bunosky, 1993;Wurm et aI., 1993). They are also consistent with results of object identification and classification tasks showing that color facilitates reaction time for items that have learned colors (Davidoff & Ostergaard, 1988;Murphy, 1991;Ostergaard & Davidoff, 1985;Price & Humphreys, 1989;Tanaka & Bunosky, 1993). cific color value.…”
Section: Representation Of Colorsupporting
confidence: 76%
“…In both classification and identification tasks, advantages for color effects are observed most consistently for well-learned items. For example, in object identification tasks, color decreases reaction time only for natural objects, not for geometric shapes (Davidoff& Ostergaard, 1988;Ostergaard & Davidoff, 1985;Price & Humphreys, 1989). Similarly, subjects are faster to respond to high color-diagnostic items, such as a yellow banana, than to low color-diagnostic items, such as a red hammer (Tanaka & Bunosky, 1993).…”
Section: Representation Of Colormentioning
confidence: 99%
“…In addition, it was demonstrated by Price and Humphreys (1989) that brightness/texture gradients (photographic detail) aVect object recognition and naming. Other studies have found that appropriately colored objects are recognized faster than monochrome objects and inappropriately colored objects (Naor-Raz, Tarr, & Kersten, 2003;Price & Humphreys, 1989) or that color does not aVect categorical judgments but the facilitation occurs in object naming tasks (DavidoV & Ostergaard, 1988). On the other hand, Bierderman and Ju (1988) argue that edge-based representations are crucial for object recognition and the objects should be recognized as easily when represented by edge information as when represented by other types of information (e.g., color photos, which contain surface information such as color, texture, and relative brightness).…”
Section: Introductionmentioning
confidence: 99%
“…Algunos investigadores han postulado la importancia de los detalles de la superficie tales como el color y la textura (Davidoff & Ostergaard, 1988). Las primeras investigaciones no reportaban diferencias en el desempeño de sujetos controles en tareas semánticas utilizando dibujos en blanco y negro o con color (Davidoff & Ostergaard, 1988;Ostergaard & Davidoff, 1985), así como tampoco en los tiempos requeridos para denominar dibujos lineales simples o fotografías en color (Biederman & Ju, 1988). Bastaba la forma del dibujo para acceder a la representación conceptual.…”
unclassified